2021
DOI: 10.1137/20m1326751
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Robust Preconditioning by Congruence for Multiple-Network Poroelasticity

Abstract: The mechanical behavior of a poroelastic medium permeated by multiple interacting fluid networks can be described by a system of time-dependent partial differential equations known as the multiple-network poroelasticity (MPET) equations or multiporosity/multipermeability systems. These equations generalize Biot's equations, which describe the mechanics of the one network case. The efficient numerical solution of the MPET equations is challenging, in part due to the complexity of the system and in part due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…A main challenge for these equations is the construction of solvers that scale properly for nearly incompressible solids where the Lam\' e dilation modulus tends to infinity, as well as in the case of nearly incompressible fluids, for which the constrained specific storage coefficient approaches zero, or the nearly impermeable regime where the hydraulic conductivity is very small. These scenarios entail not only a complication at the practical and implementation level, but also a difficulty inherent to the functional setting of the abstract formulation (see, e.g., [31,18,43]). In more detail, for almost incompressible solids (\lambda \gg \mu ), the primal form of the elasticity equation, used in (1.1a), here scaled by \lambda , - \bfnabla \cdot \Bigl( 2 \mu \lambda \bfitvar (\bfitu ) + (\nabla \cdot \bfitu )I \Bigr) = \bfitb in \Omega , is known to suffer from locking when using standard elements such as Lagrange elements.…”
mentioning
confidence: 99%
“…A main challenge for these equations is the construction of solvers that scale properly for nearly incompressible solids where the Lam\' e dilation modulus tends to infinity, as well as in the case of nearly incompressible fluids, for which the constrained specific storage coefficient approaches zero, or the nearly impermeable regime where the hydraulic conductivity is very small. These scenarios entail not only a complication at the practical and implementation level, but also a difficulty inherent to the functional setting of the abstract formulation (see, e.g., [31,18,43]). In more detail, for almost incompressible solids (\lambda \gg \mu ), the primal form of the elasticity equation, used in (1.1a), here scaled by \lambda , - \bfnabla \cdot \Bigl( 2 \mu \lambda \bfitvar (\bfitu ) + (\nabla \cdot \bfitu )I \Bigr) = \bfitb in \Omega , is known to suffer from locking when using standard elements such as Lagrange elements.…”
mentioning
confidence: 99%
“…The iterative approach has traditionally been preferred due to the potentially high cost of solving the coupled nonlinear equations. However, scalable preconditioners for the fully-coupled poroelastic problem (Piersanti et al, 2021) and high performance implementations such as in the MOOSE Framework (Gaston et al, 2009;Andrs et al, n.d.), have demonstrated that a fully coupled approach can be both performant and flexible. Along with MOOSE itself, applications built off of MOOSE have taken advantage of the modular nature of the code to produce fully coupled finite element multiphysics.…”
Section: Coupled Modelingmentioning
confidence: 99%
“…Preconditioning by congruence. When next turning to the efficient solution of the MPET equations via preconditioned iterative methods, an interesting puzzle appeared with a charming solution motif [27,28]. To illustrate, consider a coupled Darcy flow with exchange system like (9) written as…”
Section: The Incompressible Mpet Equationsmentioning
confidence: 99%
“…This observation gives a direct construction for P in terms of the eigenvectors of K −1 E. The transformed system is then block-diagonal and easily preconditioned with condition numbers that are uniform for a range of exchange and conductance parameters [28]. Interestingly, the construction extends to the MPET system [27].…”
Section: The Incompressible Mpet Equationsmentioning
confidence: 99%